Evaluation of Antihypertensive Medication Suitability at Bandung-Based General Hospital August-October 2024 - Daffa Anjabtsawa; Ellin Febrina; Annisa Desy Aryanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Pharmaceutical services in hospitals must comply with the standards set forth in Minister of Health Regulation No. 72 of 2016 to ensure the safe, effective, and efficient use of medications. One crucial aspect of clinical pharmacy services is evaluating the appropriateness of drug use in accordance with the National Formulary (Fornas), particularly in antihypertensive therapy, which is widely used in clinical practice. This study aims to evaluate the conformity level of antihypertensive drug use with Fornas at Bandung-Based General Hospital and analyze its economic impact. This research is a retrospective descriptive study that collects data on antihypertensive drug use from various service units from August to October 2024. The analysis was conducted by calculating the percentage of conformity based on the number of drug units used compared to the Fornas list, as well as assessing the economic value of the drugs utilized. The results showed a very high adherence rate to Fornas, with the highest conformity percentage reaching 99.88% in September 2024 and the lowest at 99.81% in August 2024, surpassing the minimum compliance standard of 80% set by the Hospital Minimum Service Standards. These findings reflect the effectiveness of the National Formulary policy and the hospital's commitment to rational therapy. Collaboration among pharmacists, doctors, and the medical team, along with continuous education, is necessary to ensure safe, regulatory-compliant, and efficient therapy.